Clinical Estimation of the Duration of Pregnancy in Legal Abortion—Are Doctors Biased by their Knowledge of the Duration of Amenorrhoea? - Gjørup, Th.; Saurbrey, Nina; Hermann, N. (Methods of Information in Medicine, 1984)
In 35 women referred for induced abortion, the duration of pregnancy was stated with an accuracy of one week on the basis of the gynaecologic examination. This was done by one doctor with knowledge of the duration of amenorrhoea (clinical estimate) and by one doctor without this knowledge (“blind” estimate). Agreement was found between the duration of amenorrhoea and the duration of pregnancy for 89% of the clinical estimates and for 46% of the “blind” estimates. Prior to the study the doctor who made the “blind” estimates had—with knowledge of the duration of amenorrhoea—examined 26 similar women and had obtained agreement as to 88% of her estimates. For the clinical estimates, the difference between the duration of amenorrhoea and the duration of pregnancy did not exceed one week, whereas for the “blind” estimates, it amounted to as much as 3 weeks. It is concluded that doctors’ clinical estimate of the duration of pregnancy is influenced by their knowledge of the duration of amenorrhoea.
Keywords: Bias; Duration of Amenorrhoea; Duration of Pregnancy